PROCEDURE TEXT WEBSITE (WETROSE) AS A MEDIUM TO IMPLEMENT MERDEKA BELAJAR PROGRAM FOR JUNIOR HIGH SCHOOL STUDENTS - Masnuatul Hawa; Sutrimah Sutrimah; Muhamad Sholehhudin; Abdul Ghoni Asror (Proceeding International Conference on Digital Education and Social Science, 2022)
This study aimed to (1) describe and explain the process of using WETROSE (Procedural Text Website) as a medium to implement the Merdeka Belajar Program for junior high school students and (2) describe the results of using the procedure text website (WETROSE) to implement the Merdeka Belajar Program for junior high school students. This study employed a qualitative descriptive method. The findings of this study are as follows: (1) the use of WETROSE has several stages, i.e., pre-test, inviting students to learn through WETROSE level 1, inviting students to learn through WETROSE level 2, and post-test; (2) after learning through WETROSE, it was discovered that there was a pleasant atmosphere in the learning process, there was flexibility for students to carry out the procedure text learning process according to their level of ability, and students felt satisfaction. Based on the research, it is concluded that the Procedure Text Website (WETROSE) can make learning more enjoyable and is capable of assisting in the implementation of Merdeka Belajar Program in junior high schools.